2020
DOI: 10.3390/foods9081055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultrasound Treatment and pH-Shifting on Physicochemical Properties of Protein-Enriched Barley Fraction and Barley Protein Isolate

Abstract: Ultrasonication alone or in combination with a pH-shifting method could be applied as means for improving the techno-functional properties and performance of barley protein ingredients in liquid food matrix. Ultrasound technology was utilised with and without pH-shifting to 3, 7 and 9 aiming at investigating their impact on primary protein structure, protein solubility, particle size and colloidal stability of an air-classified protein-enriched barley fraction and a barley protein isolate. Shifting the pH of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 51 publications
(119 reference statements)
1
16
0
Order By: Relevance
“…Extraction of quinoa proteins was carried out as described by Silventoinen, & Sozer [ 22 ]. The quinoa seeds was crushed, sifted using a 60-mesh sieve, and degreased with petroleum ether (Auto fat analyzer, Sex 406, Jinan Haineng Instrument Co., Ltd., Jinan, China).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of quinoa proteins was carried out as described by Silventoinen, & Sozer [ 22 ]. The quinoa seeds was crushed, sifted using a 60-mesh sieve, and degreased with petroleum ether (Auto fat analyzer, Sex 406, Jinan Haineng Instrument Co., Ltd., Jinan, China).…”
Section: Methodsmentioning
confidence: 99%
“…The pulse protein has an important role in nutrition, and its techno-functional properties have a potential impact on the food system . In the food industry, proteins are processed and modified using physical, chemical, and enzymatic methods to improve their functional properties and food applications. The modification of several proteins including peanut protein, fava bean protein, soy protein, rice protein, rapeseed protein, and barley protein using different processing treatments was done to improve their functional properties and to boost their application in the development of novel foods. Incorporation of protein derived from germinated chickpea was found to enhance the qualities of the developed product, including nutritional, sensory, and consumer acceptability .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ultrasound treatment has been shown to enhance the solubility of proteins in several studies [ 8 , 16 , 17 ]. Furthermore, it was shown that the efficiency of the pH shifting processing on pea protein [ 8 ], soy protein [ 6 ], and barley protein isolate [ 18 ] was enhanced when combined with ultrasound treatment.…”
Section: Introductionmentioning
confidence: 99%